Evaluating diagnostic tools for phosphorus and sulfur management in corn - Roa Acosta, Gustavo Adolfo (Kansas State University, 2024)
Efficient management of essential nutrients, such as phosphorus (P) and sulfur (S), is critical for maximizing corn productivity. This study aimed at enhancing corn production by evaluating diagnostic tools for nutrient management and optimizing fertilization practices, focusing on P and S nutrients. Studies were conducted across 26 sites in Kansas. The first project focuses on phosphorus nutrition. Field experiments involved varying phosphorus fertilizer rates of 34, 67, 101, and 135 kg P₂O₅ ha⁻¹, plus a control. At the V6 stage, whole plant tissue samples and normalized difference vegetative index (NDVI) readings were collected. At the R1 stage, ear leaf samples and soil plant analysis development (SPAD) readings were collected. Results indicated that the average critical P tissue concentrations (CPTC) in the whole plant at V6 and the ear leaf at R1 were 4.9 g kg⁻¹ and 3.8 g kg⁻¹, respectively. As the P tissue concentration increases, the optimum fertilizer recommendation rate decreases. Correlation shows that NDVI showed limited effectiveness in assessing phosphorus levels or yield; the SPAD correlation with yield displayed some potential for further exploration. A moderate correlation and linear relationship were found between plant P tissue concentration at V6 and leaf P tissue concentration at R1 (r =0.49 and R² = 0.24). This study offers insights into phosphorus management in corn through CPTC and fertilizer calibration and highlights diagnostic tool limitations. In the second study, sulfur fertilizer rates were applied at 45 kg of S ha⁻¹, plus a control. Whole plant samples and NDVI were collected at the V6 stage, and ear leaf samples and SPAD were collected at the R1 stage. A whole plant sample at the R6 stage and grain yield were collected. Results indicated no correlation between NDVI at V6 and S tissue concentration or yield. There is a correlation between SPAD at R1 and S tissue concentration, as well as with yield. Sulfur application increases S tissue concentration for the different stages V6, R1, R6, and grain, as well as S uptake at V6 and total S uptake across sites. A positive relationship was found between the total S uptake and yield, with an R² value of 0.72. The analysis revealed the mean agronomic sulfur use efficiency across sites was 1.4 kg kg⁻¹. The apparent sulfur recovery efficiency had a mean of 2.2 % across sites. This study highlights the importance of sulfur in corn. The studies provide insights into P and S nutrient management for corn production in Kansas.
Keywords: Corn productivity; Phosphorus management; Sulfur fertilization; Diagnostic tools